GAINING PURCHASE INTENTION BY ELECTRONIC WORD OF MOUTH AND BRAND AMBASSADOR - Pidada, Ida Ayu Iswari; Supartyani, Ni Wayan (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: This study examines the effectiveness of e-WOM and brand ambassador toward purchase intention of Sasa product through the promotion of